Empowering TPQ/Madin Students through Public Speaking Mentoring Based on Asset-Based Community Development (ABCD) - Yuni Masrifatin (STAI Miftahul ULa Nganjuk, 2025)
This article discusses a community service program focused on enhancing the skills and self-confidence of children at Quranic Education Institutions (TPQ/Madin) in Senggowar Village. The initiative employed the Asset-Based Community Development (ABCD) approach, which leverages existing community assets as the primary foundation for development. The key assets identified were the TPQ/Madin institutions themselves and the latent potential of the students. The program involved structured mentoring and training in public speaking, integrated with Qur'anic values. Activities included teaching assistance, speech and poetry training, and inter-TPQ competitions. The results indicated a significant increase in the students' confidence, communication abilities, and willingness to express themselves in public. The program successfully demonstrated that by focusing on and developing internal assets, it is possible to foster a generation of Qur'anic youth who are not only religiously knowledgeable but also confident and articulate, thereby contributing to positive social change within the community.